Effects of Thyrotropin-Releasing Hormone on Urethral Closure Pressure in Females with Voiding Dysfunction - Hajebrahimiurnal, Sakineh; Madaen, Seyed Kazem; Sheikhzadeh, Peymaneh (Urology Journal, 2009)
Purpose: To evaluate the effect of intravenous thyrotropin releasing hormone (TRH) on the urethral closure pressure (UCP). Materials and Methods: Twenty-two female patients with either bladder outlet obstruction (BOO) or detrusor under activity were included in this study. They divided into two study and control groups randomly. Twelve patients in study group received 200 microgr of TRH intravenously and patients in control group received intravenous normal saline as placebo. Standard urethral pressure profilometry was performed before injection and after injection at 5, 10, 20 and 30 minutes. Functional profile length (FPL), maximum urethral closure pressure (MUCP), and urethral closure pressure at the proximal quarter of the FPL (1/4 FLP) and at the distal quarter of FPL (3/4 FLP) were measured in both groups. Results: The mean age of the study and control groups were 41.61 ± 21.7 years and 43.59 ± 19 years respectively .The study and control groups included 5 BOO and 6 detrusor under activity and 4 BOO and 5 detrusor under activity respectively. The mean peak flow rate was 5.69 ± 8.4 ml/s in the study group and 6.31 ± 81 ml/s in control group. There wasn't significant difference between two groups. Mean maximum urethral closure pressure demonstrated no significant difference in two groups before and after TRH injection, but a marked reduction in 3/4 UCP and 3/4 FPL in patients after TRH injection was seen. Conclusion: TRH injection significantly reduces the distal urethral pressure.